Perjanjian sewa Pelaksanaan Perjanjian Sewa-Menyewa Lahan Di Area Sekitar Pantai (Studi Di Kecamatan Maluk,KSB): perjanjian sewa lahan - Desy Rahmadani, Ayu; Rahman, Arief (Faculty of Law, University of Mataram, 2024)
This research aims to determine the legal position of the land subject tothe rental agreement and to determine the implementation of land leasing in thearea around Maluk Beach, West Sumbawa Region. The type of research used isempirical legal research, with the use of the statute approach, conceptualapproach, and sociological approach as the methods. The result of this researchdetermines that the legal position of the research object's land is land borderingthe coast it is controlled directly by the state. The Pasir Putih village governmentis utilizing coastal border land supported by the regulations regarding the tourismdevelopment master plan for the West Sumbawa district. The land useimplementation carried out is a land rental agreement, in the written form by thePasir Putih village government and signed by the land lessee.